Building and sustaining agile information systems - Desouza, Kevin C. (Henry Stewart Talks, 2011)
Building and Sustaining Agile Information Systems, What are Agile Organizations, The 4WD Model for Agile Organizations, Information and Knowledge, Work and Technology, Designing Agile Information Organizations, Sustaining Agile Information Organizations, Five Stages of Organizational Maturity, Risk in Designing Agile Information Organizations, Ten Guidelines for Building Agile Information Organizations